Traditional Muslim Birth Preparation Practices in Bali and Childcare Arrangements among Working Mothers - Aprianti, Neli; Indrawati, Indrawati; Maruddani, Raoda Tul Jannah Maruddani (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2025)
Parenting is an attitude carried out by parents or adults around a child to care for and educate the child. Then, custom is something that applies in a place to be implemented. This study aims to determine the procession of preparation for the birth of traditional Muslims in the village of Tegal Badeng, Negara District, Bali. Starting from before birth to welcoming the birth of a child and the daily care process for mothers who work for two families with early childhood. This study uses a qualitative method with a case study approach. The informants in this study were three mothers who worked as factory employees and the local community. This study found how the initial procession started from the child in the womb until the process of welcoming the birth of a child and the care provided by three informants. There are traditional and religious rituals in the procession before birth, namely holding a seven-month event and in welcoming the birth of a child, a nelai event is held. In addition to preparation for birth, in the caregiving process the three informants separated between care and their working hours. Family involvement is a factor supporting the success of the birth preparation procession to parenting.